Major Bleeding Risk in Atrial Fibrillation Patients Co-Medicated With Non-Vitamin K Oral Anticoagulants and Antipsychotics - Chen, Chiung-Mei; Chang, Kuo-Hsuan; Wang, Chun-Li; Tu, Hui-Tzu; Huang, Yu-Tung; Wu, Hsiu-Chuan; Chang, Chien-Hung; Chang, Shang-Hung (Frontiers in Pharmacology, 2022)
Major bleeding risks associated with non-vitamin K oral anticoagulants (NOACs) used with and without concurrent antipsychotics in patients with non-valvular atrial fibrillation (AF) were assessed. A total of 98,863 patients with non-valvular AF receiving at least one NOAC prescription from Taiwan’s National Health Insurance database were enrolled. Major bleeding was defined as a primary diagnosis of intracranial or gastrointestinal hemorrhage or bleeding at other sites. The adjusted incidence rate difference (AIRD) per 1,000 person-years and adjusted rate ratio of major bleeding were estimated using Poisson regression and inverse probability of treatment weighting using the propensity score. A total of 8,037 major bleeding events occurred during 705,521 person-quarters with NOAC prescriptions. Antipsychotics were used in 26.35% of NOAC-exposed patients. Compared to using NOAC alone, co-medication of either typical (AIRD: 79.18, 95% confidence interval [CI]: 70.63–87.72) or atypical (AIRD: 40.5, 95% CI: 33.64–47.35) antipsychotic with NOAC had a significant increase in the adjusted incidence rate per 1,000 person-years of major bleeding. The concomitant use of a NOAC with chlorpromazine (AIRD: 103.87, 95% CI: 51.22–156.52), haloperidol (AIRD: 149.52, 95% CI: 125.03–174.00), prochlorperazine (AIRD: 90.43, 95% CI: 78.55–102.32), quetiapine (AIRD: 44.6, 95% CI: 37.11–52.09), or risperidone (AIRD: 41.55, 95% CI: 22.86–60.24) (All p < 0.01) showed a higher adjusted incidence rate of major bleeding than using NOACs alone. The concomitant use of typical (chlorpromazine, haloperidol, or prochlorperazine) or atypical (quetiapine or risperidone) antipsychotic with NOACs was associated with a significantly increased risk of major bleeding.